IDENTIFICATION OF COMPONENTS OF (NA(+) + K(+))-ADENOSINE TRIPHOSPHATASE BY DOUBLE ISOTOPIC LABELING AND ELECTROPHORESIS - Chignell, Colin F. (1969)
A microsomal adenosine triphosphatase (ATPase) that requires both sodium and potassium ions is thought to be identical with, or an integral part of, the active cation transport system located in cell membranes. Attempts to isolate and purify (Na(+) + K(+))-ATPase have met with limited success because solubilization of microsomal protein causes partial, if not complete, loss of enzymatic activity. We now report the isolation from rat kidney microsomes of proteins which, though enzymatically inactive, could still be identified as components of the (Na(+) + K(+))-ATPase system. Phosphoproteins known to be intermediates in the hydrolysis of ATP by (Na(+) + K(+))-ATPase were prepared by incubating rat kidney microsomes with γ-labeled ATP(33) in the presence of sodium or with P(32)-orthophosphate in the presence of ouabain. After the P(32)- and P(33)-labeled microsomes had been dissolved in phenol-acetic acid-urea, the resultant solutions were mixed and subjected to polyacrylamide gel electrophoresis. The radioactivity from both phosphorus isotopes was found almost exclusively in one of the resultant 21 protein bands. In contrast, the radioactive protein from DFP(32)-labeled microsomes moved slightly faster than the radioactive protein from microsomes labeled with P(33)-orthophosphate in the presence of ouabain. DFP inhibits (Na(+) + K(+))-ATPase by reacting with a nucleophilic site at or near the active site. These results suggest that while a single protein component of (Na(+) + K(+))-ATPase accepts the terminal phosphate from ATP, the final splitting of this phosphoprotein intermediate may be catalyzed by nucleophilic sites on a second protein.